Novel Projections to the Cerebrospinal Fluid-Contacting Nucleus From the Subcortex and Limbic System in Rat - Song, Si-Yuan; Zhai, Xiao-Meng; Dai, Jia-Hao; Lu, Lei-Lei; Shan, Cheng-Jing; Hong, Jia; Cao, Jun-Li; Zhang, Li-Cai (Frontiers in Neuroanatomy, 2020)
Objective To identify the novel projections received by the cerebrospinal fluid (CSF)-contacting nucleus from the subcortex and limbic system in order to understand the biological functions of the nucleus. Methods The cholera toxin subunit B (CB), a retrograde tracer, was injected into the CSF-contacting nucleus in Sprague-Dawley rats. After 7-10 days, the surviving rats were perfused, and the whole brain and spinal cord were sliced for CB immunofluorescence detection. The CB-positive neurons in the subcortex and limbic system were observed under a fluorescence microscope, followed by 3D reconstructed with the imaris software. Results CB-positive neurons were found in the basal forebrain, septum, periventricular organs, preoptic area, and amygdaloid structures. Five functional areas including forty-six sub-regions sent projections to the CSF-contacting nucleus. However, the projections had different densities, ranging from sparse, to moderate, to dense. Conclusions According to the projections from the subcortex and limbic system, we hypothesise that the CSF-contacting nucleus participates in emotion, cognition, homeostasis regulation, visceral activity, pain and addiction. In this study, we illustrate the novel projections from the subcortex and limbic system to the CSF-contacting nucleus, which underlies the diverse and complicated circuits of the nucleus in body regulations.